Cytotoxicity Effect of Aqueous Propolis Extract of Geniotrigona thoracica Sumatrans on Colo-201 Colon Cancer Cell Line and Senescence Colo-201 Colon Cancer Cell Line Induced by Low-dose Doxorubicin - Latama, Zahra Nabila; Achadiyani, Achadiyani; Kamilah, Mutiara Mila; Putra, Ramadhani Eka; Kinasih, Ida; Faridah, Lia; Ekawardhani, Savira (Global Medical & Health Communication (GMHC), 2024)
Propolis, a resinous compound honeybees produce, demonstrates an extensive spectrum of powerful biological properties. However, the anti-cancer activity of propolis derived from Geniotrigona thoracica Sumatrans has yet to be reported. Thus, we sought to investigate the cytotoxicity of aqueous propolis extracts from Geniotrigona thoracica Sumatrans against Colo-201 colon cancer cell line and senescence Colo-201 colon cancer cell line induced by low-dose doxorubicin. This study was conducted at the Parasitology Laboratory of Human, Safety, and Environment, Universitas Padjadjaran Bandung from January to May 2024. This study assessed cell viability using the WST-1 test. Non-induced Colo-201 cells were treated with an aqueous extract of propolis (AEP) 100 ppm, or 5-fluorouracil (5-FU) 5 mg/ml as the positive control or water as a vehicle on untreated control. Colo-201 senescence was induced by doxorubicin 0.1 µM for three days. Doxorubicin-induced Colo-201 senescence was then treated with AEP 100 ppm, with 5-FU 5 mg/ml as the positive control, or with the combination of AEP 100 ppm and 5-FU 5 mg/ml, or water as a vehicle on untreated control. The data were analyzed using SPSS version 25.0, a one-way ANOVA, and Tukey’s post hoc test. The results showed that AEP has cancer-killing effects on Colo-201 cells and Colo-201 senescent cells induced by low-dose doxorubicin. AEP-treated Colo-201 cells and Colo-201 senescent cells induced by low-dose doxorubicin viability were significantly reduced to 37.15% and 13.72%, respectively, although slightly higher than those of the 5-FU-treated one at this concentration. There was also a decrease in the cancer-killing effect of 5-FU from 88.55% in non-induced Colo-201 cells to 41.5% in the doxorubicin-induced Colo-201 senescence model. In conclusion, aqueous extract of propolis from Geniotrigona thoracica Sumatrans showed cancer-killing-effects both on the Colo-201 colon cancer cell line and senescence Colo-201 colon cancer cell line induced by low-dose doxorubicin.